Merging Ion Concentration Polarization between Juxtaposed Ion Exchange Membranes to Block the Propagation of the Polarization Zone - Kim, Minyoung; Rhee, Hyunjoon; Kang, Ji Yoon; Kim, Tae Song; Kwak, Rhokyun (JOURNAL OF VISUALIZED EXPERIMENTS, 2017)
The ion concentration polarization (ICP) phenomenon is one of the most prevailing methods to preconcentrate low-abundance biological samples. The ICP induces a noninvasive region for charged biomolecules ( i.e., the ion depletion zone), and targets can be preconcentrated on this region boundary. Despite the high preconcentration performances with ICP, it is difficult to find the operating conditions of nonpropagating ion depletion zones. To overcome this narrow operating window, we recently developed a new platform for spatiotemporally fixed preconcentration. Unlike preceding methods that only use ion depletion, this platform also uses the opposite polarity of the ICP ( i.e., ion enrichment) to stop the propagation of the ion depletion zone. By confronting the enrichment zone with the depletion zone, the two zones merge together and stop. In this paper, we describe a detailed experimental protocol to build this spatiotemporally defined ICP platform and characterize the preconcentration dynamics of the new platform by comparing them with those of the conventional device. Qualitative ion concentration profiles and current-time responses successfully capture the different dynamics between the merged ICP and the stand-alone ICP. In contrast to the conventional one that can fix the preconcentration location at only similar to 5 V, the new platform can produce a target-condensed plug at a specific location in the broad ranges of operating conditions: voltage ( 0.5-100 V), ionic strength ( 1-100 mM), and pH ( 3.7-10.3).